A Survey of Cancer Pain Management Knowledge and Attitudes of British Columbian Physicians. (1st December 2004) - Gallagher, R; Hawley, P; Yeomans, W
Abstract : INTRODUCTION: There are many potential barriers to adequate cancer pain management, including lack of physician education and prescription monitoring programs. The authors surveyed physicians about their specific knowledge of pain management and the effects of the regulation of opioids on their prescribing practices. METHODS: A questionnaire was mailed out to British Columbia physicians who were likely to encounter cancer patients. The survey asked for physicians' opinions about College of Physicians and Surgeons of British Columbia regulation and other issues related to their prescribing practices, and assessed basic knowledge of cancer pain management. RESULTS: There was a 69% return rate with a total of 4618 evaluable responses. There was a significant difference among medical disciplines, years in practice, number of chronic pain patients seen and size of community of practice. The highest knowledge scores were achieved by oncologists and the lowest scores were from surgeons. Those who practiced in smaller communities had a higher average knowledge score. Those who felt their knowledge about cancer pain was inadequate scored lower than those who felt their knowledge was adequate. The questions most frequently answered incorrectly (or by 'don't know') were those about equianalgesic dosing (68%) and adequate breakthrough dosing (45%), revealing knowledge deficiencies that would significantly impair a physician's ability to manage cancer pain. CONCLUSIONS: The details of opioid prescribing are crucial areas to target education for cancer pain management. The surveyed physicians accepted the need for regulation of opioid prescribing with very few being fearful of scrutiny from the College of Physicians and Surgeons of British Columbia. However, the inconvenience of the triplicate prescription pad was more of a barrier to prescribing, it being of concern to 20% of respondents, particularly surgeons and medical specialists.